Estimation in Classroom Setting - Tiwari, Rinki; Patel, R. C. (THE PRIMARY TEACHER, 2019)
Each country has its particular aims and objectives of education. Those objectives are contextual as per the country. But one common objective of most of the countries is to relate the knowledge acquired in classroom to combat the real-life issues and concerns. One important topic which comes to the scene is estimation. It involves clear understanding and application of knowledge for problem solving. This paper is an attempt to implement the conceptual understanding of classroom knowledge to different circumstances, scope of Estimation in the curriculum and teachers’ role in enhancing the estimation ability of students are the points highlighted in this paper. Estimation focuses on the process rather than product. It assumes that if process can be given a right direction, product itself will shift toward perfection.